2020
DOI: 10.1016/j.isci.2020.101278
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-8 Enhances T cell Response by Promotion of Antigen Internalization and Processing

Abstract: Gal-8-glycan interactions at APC surface induce soluble antigen internalizationGal-8 and antigen are internalized together in early endosomal compartments Gal-8 favors antigen proteolytic processing and presentation in the context of MHC-II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…They can also directly interact with the SARS-CoV-2 viruses and affect viral replication. Alternatively, Gals may modulate antigen presentation/processing and stimulate the elicitation of T cell response in a lectin-dependent manner ( 75 ). Further studies are required to better understand the role of viral factors and Gals in the induction of cytokine release syndrome and provide evidence to better understand SARS-CoV-2 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They can also directly interact with the SARS-CoV-2 viruses and affect viral replication. Alternatively, Gals may modulate antigen presentation/processing and stimulate the elicitation of T cell response in a lectin-dependent manner ( 75 ). Further studies are required to better understand the role of viral factors and Gals in the induction of cytokine release syndrome and provide evidence to better understand SARS-CoV-2 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these interesting studies on the role of Gal-8, it is important to mention that its role in cancer progression is not black-and-white. Although similar to other galectins, Gal-8 can induce apoptosis in immature T cells [ 101 , 102 ], recent studies in various experimental systems by Maria Tribulatti’s group suggest that Gal-8 has important immunostimulatory functions in peripheral naïve T cells and promotes the uptake of antigens by antigen-presenting cells [ 103 , 104 ]. Interestingly, Gal-3 has been shown to inhibit the immunostimulatory effect of Gal-8 on naïve T cells [ 105 ], emphasizing the need to develop galectin inhibitors that are very specific.…”
Section: The Case Of Galectin-8mentioning
confidence: 99%
“…Some additional information can be drawn from other (non-tumoral) experimental models. Indeed, galectin-8 promotes all steps of antigen presentation from antigen binding, internalization, processing [ 211 ], and maturation of dendritic cells [ 212 , 213 ]. Studies with galectin-8 deficient antigen-presenting cells confirmed the relevance of such functions in pathophysiology [ 212 ].…”
Section: Introductionmentioning
confidence: 99%